Total Synthesis of Lycogarubin C and Lycogalic Acid - Oakdale, James S. (2010)
[Image: see text] Two complementary concise total syntheses of lycogarubin C (1) and lycogalic acid (2, aka chromopyrrolic acid) are detailed utilizing a 1,2,4,5-tetrazine → 1,2-diazine → pyrrole Diels–Alder strategy and enlisting acetylenic dienophiles.